Pelatihan Penggunaan Media Sosial Menuju Perbaikan Ekonomi Di Era Digitalisasi Bagi Ibu-Ibu Aisyiyah Ranting Kampung Kebon Sawangan Depok - Ujang Syaifudin Sumaji; Adi Supriadi; Muhammad Arif Adriyanto (Universitas Pamulang, 2022)
Aisyiyah recitation mothers in the Cinangka subdistrict, Depok city, have not been able to take advantage of their social media so that it can be economically valuable. So far, mothers only use cellphones to communicate with friends and family without economic value. This is due to the lack of understanding about the proper use of cellphones which can have economic value. The community service entitled